The Role of Islamic Financial Institutions in Facilitating National Economic Development - Febriansyah Febriansyah; Siti Maryam; Gita Susanti; Amrita Nayak (Economica Insight, 2026)
Islamic Financial Institutions (IFIs) play a strategic role in supporting national economic development through financing mechanisms based on the principles of justice, sustainability, and inclusivity. In 2025, the contribution of IFIs has become increasingly relevant alongside the growing demand for development financing, the strengthening of the real sector, and the promotion of sustainable and inclusive economic growth. This study aims to analyze the role of IFIs in facilitating Indonesia’s national economic development by examining their financial intermediation function, support for Micro, Small, and Medium Enterprises (MSMEs), financial system stability, and social contributions through zakat, infaq, sadaqah, and waqf (ZISWAF) instruments. The research method employed is a literature study using a descriptive-analytical approach toward various scientific publications, official institutional reports, and related regulations. The findings indicate that IFIs play a significant role in promoting equitable economic growth through productive sector financing, increased financial inclusion, and the strengthening of the national Islamic economy. However, challenges related to Islamic financial literacy, product innovation, and policy synergy still need to be addressed to optimize the sustainable role of IFIs.